2001
DOI: 10.1046/j.0953-816x.2001.01759.x
|View full text |Cite
|
Sign up to set email alerts
|

Catalepsy induced by a blockade of dopamine D1 or D2 receptors was reversed by a concomitant blockade of adenosine A2A receptors in the caudate‐putamen of rats

Abstract: The present study sought to determine, in more detail, the effects of an unselective and a selective adenosine A(2A) receptor blockade on catalepsy induced by a blockade of dopamine D1 or D2 receptors in rats. The results demonstrated that systemic administration of the unselective A1/A2 receptor antagonist, theophylline and the selective A(2A) receptor antagonist, CSC potently reversed catalepsy induced by a systemic D2 receptor blockade with raclopride or by a bilateral blockade of D2 receptors in the caudat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
71
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(79 citation statements)
references
References 44 publications
8
71
0
Order By: Relevance
“…As shown by in situ hybridization and binding studies (Martinez-Mir et al, 1991;Schiffmann et al, 1991;Svenningsson et al, 1998), the A 2A receptor is coexpressed with DA D 2 receptors in the striatopallidal GABAergic neurons, which contain enkephalin and originate in the so-called striatal efferent indirect pathway (Fink et al, 1992). Behavioral data support the strong A 2A -D 2 receptor interactions to explain the enhancement of the antiParkinsonian effects of DA agonists in rodent models of PD (Pinna et al, 1996;Fenu et al, 1997;Koga et al, 2000;Hauber et al, 2001).…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…As shown by in situ hybridization and binding studies (Martinez-Mir et al, 1991;Schiffmann et al, 1991;Svenningsson et al, 1998), the A 2A receptor is coexpressed with DA D 2 receptors in the striatopallidal GABAergic neurons, which contain enkephalin and originate in the so-called striatal efferent indirect pathway (Fink et al, 1992). Behavioral data support the strong A 2A -D 2 receptor interactions to explain the enhancement of the antiParkinsonian effects of DA agonists in rodent models of PD (Pinna et al, 1996;Fenu et al, 1997;Koga et al, 2000;Hauber et al, 2001).…”
Section: Introductionmentioning
confidence: 82%
“…Conversely, A 2A receptor agonists prevented the rotational behavior produced by apomorphine (Morelli et al, 1994). Recent evidence suggest that the antagonism of striatal A 2A receptors may represent an alternative therapeutic approach to PD and systemic or intrastriatal infusions of selective A 2A receptor antagonists, CSC or MSX-3, respectively, were found to reverse the cataleptic response induced by DA receptors blockade (Hauber et al, 1998(Hauber et al, , 2001. When tested in monkeys treated with 1-methyl-4-phenyl-1,2,5,6,-tetrahydropyridin (MPTP), the A 2A antagonist KW-6002 produced a significant improvement in motor disability (Kanda et al, 1998) and potentiated L-DOPA-mediated effects (Grondin et al, 1999).…”
Section: Adenosine a 2a Receptors Antagonism As Anti-parkinsonian Strmentioning
confidence: 99%
See 1 more Smart Citation
“…In these striatal areas, there is considerable evidence of a functional interaction between dopamine D 2 and adenosine A 2A receptors (Fink et al 1992;Ferré 1997;Hillion et al 2002;Fuxe et al 2003). This interaction has typically been investigated in connection with neostriatal motor functions that are potentially related to parkinsonism Svenningsson et al 1999;Ferré et al 2001;Hauber et al 2001;Morelli and Pinna 2002;Jenner 2003Jenner , 2005Pinna et al 2005). In these studies, adenosine A 2A receptor antagonists have been shown to exert effects consistent with antiparkinsonian actions in animal models (Ferré et al , 2001Hauber et al 2001;Wardas et al 2001;Jenner 2003;Correa et al 2004;Pinna et al 2005;Ishiwari et al 2007), and adenosine A 2A receptor antagonists are being evaluated as antiparkinsonian agents in human clinical trials (Jenner 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This interaction has typically been investigated in connection with neostriatal motor functions that are potentially related to parkinsonism Svenningsson et al 1999;Ferré et al 2001;Hauber et al 2001;Morelli and Pinna 2002;Jenner 2003Jenner , 2005Pinna et al 2005). In these studies, adenosine A 2A receptor antagonists have been shown to exert effects consistent with antiparkinsonian actions in animal models (Ferré et al , 2001Hauber et al 2001;Wardas et al 2001;Jenner 2003;Correa et al 2004;Pinna et al 2005;Ishiwari et al 2007), and adenosine A 2A receptor antagonists are being evaluated as antiparkinsonian agents in human clinical trials (Jenner 2005). More recently, researchers have begun to identify potential motivational functions of adenosine A 2A receptors (O'Neill and Brown 2006;Harper et al 2006;Cabeza de Vaca et al 2007;Farrar et al 2007).…”
Section: Introductionmentioning
confidence: 99%